Some aspects of (net) emigration from Northern Ireland - Slattery, D. G.; Jones, R. M. (Statistical and Social Inquiry Society of Ireland, 1979)
This paper reports on one aspect ? migration ? of on-going work in the Central Economic Service directed towards a fuller understanding of the Northern Ireland economy. As is indicated in the text, the present results are tentative. They are presented here in the hope of stimulating interest and discussion.
Read before the Society, 12 March 1979
Keywords: Net emigration trends in Northern Ireland; Demographic trends in Northern Ireland; 314.15